Layanan pendidikan pada siswa hiperaktif - Reno Rezita Aprilia (Yinyang: Jurnal Studi Islam Gender dan Anak, 2020)
The success of the education process in a school is influenced by many factors. Factors that come for example from the teacher, students, curriculum, and other social environments. But the most important factor comes from two figures, namely teachers and students, especially in learning activities. In the teaching and learning process, the teacher finds the diversity of individual students whose results can be seen many differences from one student to another student. Seeing the characteristics of each of these students, it is not uncommon for teachers to be exposed to students who have hyperactive behavior. The condition of such children is usually very difficult for teachers to manage and educate them, aside from the fact that they are very difficult to calm down, also because hyperactive children often interfere with other students. Examples of hyperactive student behavior, like to interrupt teachers or friends, difficult to follow the learning, always feel bored, annoying friends and others. Therefore, the learning achievement of hyperactive children is also classified as less than the maximum. The definition of hyperactivity itself is a person's behavior that shows an attitude of not wanting to be quiet, not paying attention and impulsive. But hyperactive children still have the right to gain knowledge. The existence of educational services through formal institutions such as in Madrasah Ibtidaiyah, the efforts obtained include: teacher strategies and methods in the learning process, creativity development, talent development activities, the use of attractive media, rewards and punishment.